Factors associated with long‐term graft survival in pediatric kidney transplant recipients. (11th March 2021) - Anand, Adrish; Malik, Tahir H.; Dunson, Jordan; McDonald, Malcolm F.; Christmann, Caroline R.; Galvan, Nhu Thao Nguyen; O'Mahony, Christine; Goss, John A.; Srivaths, Poyyapakkam R.; Brewer, Eileen D.; Rana, Abbas
Abstract: Pediatric kidney transplant recipients generally have good outcomes post‐transplantation. However, the younger age and longer life span after transplantation in the pediatric population make understanding the multifactorial nature of long‐term graft survival critical. This investigation analyzes factors associated with 10‐year survival to identify areas for improvement in patient care. Kaplan‐Meier with log‐rank test and univariable and multivariable logistic regression methods were used to retrospectively analyze 7785 kidney transplant recipients under the age of 18 years from January 1, 1998, until March 9, 2008, using United Network for Organ Sharing (UNOS) data. Our end‐point was death‐censored 10‐year graft survival after excluding recipients whose grafts failed within one year of transplant. Recipients aged 5–18 years had lower 10‐year graft survival, which worsened as age increased: 5–9 years (OR: 0.66; CI: 0.52–0.83), 10–14 years (OR: 0.43; CI: 0.33–0.55), and 15–18 years (OR: 0.34; CI: 0.26–0.44). Recipient African American ethnicity (OR: 0.67; CI: 0.58–0.78) and Hispanic donor ethnicity (OR: 0.82; CI: 0.72–0.94) had worse outcomes than other donor and recipient ethnicities, as did patients on dialysis at the time of transplant (OR: 0.82; CI: 0.73–0.91). Recipient private insurance status (OR: 1.35; CI: 1.22–1.50) was protective for 10‐year graft survival. By establishing the role of age, race, and insurance status on long‐term graft survival, we hope to guide clinicians in identifying patients at high risk for graft failure. This study highlights the need for increased allocation of resources and medical care to reduce the disparity in outcomes for certain patient populations.